O ritmo de queda na desigualdade no Brasil é adequado? Evidências do contexto histórico e internacional - Sergei Suarez Dillon Soares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2008)
– The following study uses two approaches to judge whether inequality in Brazil is falling fast enough. The first is to compare the variation of the Gini coefficient in Brazil with what was observed in several countries that today belong to the Organisation for Economic Co-operation and Development (OECD) - France, Netherlands, Norway, Spain, Sweden, United Kingdom, and United States - while they built their social welfare systems during the last century. The second approach is to calculate for how long Brazil must keep up the fall in the Gini coefficient to attain the same levels of inequality of three OECD countries that can be used as a reference: Canada, Mexico, and the United States. The data indicate that the Gini coefficient in Brazil is falling 0.7 point per year and that this is superior to the rhythm of all the OECD countries analyzed while they built their welfare systems but Spain, whose Gini fell 0.9 point per year during the 1950s. The time needed to attain various benchmarks in inequality are: six years to Mexico, twelve to the United States and 24 to Canadian inequality levels. The general conclusion is that the speed with which inequality is falling is adequate, but the challenge will be to keep inequality falling at the same rate for another two or three decades.
Keywords: D31; N30; 330; Einkommensverteilung; Gini-Koeffizient; Brasilien; OECD-Staaten